EFFICACY OF A PHYSICAL EDUCATION TEACHER EDUCATION-INHERENT INJURY PREVENTION PROGRAM. Issue 7 (11th March 2014) - Goossens, L; Cardon, G; Witvrouw, E; De Clercq, D
Abstract : Background: Since physical education teacher education (PETE) students have to deal with a considerable amount of non-contact injuries to the lower limbs (Goossens et al., 2013), strategies relying on preventive exercises might reduce injury incidence in this population. Objective: Is a prevention program for injuries to the lower limbs efficacious in reducing the injury incidence and does it enhance functional performance, self-reported behaviour and consciousness, motivation and knowledge towards injury prevention?. Design: The study followed a historically controlled design with prospective injury registration and a pre-post design without control group concerning the other outcomes. Setting: Freshmen academic bachelor PETE students (±7 hours of intracurricular sports activities weekly) of three consecutive years took part in the study. Participants: The control group (CG) consisted of 128 freshmen students in academic year (AY) 2010–11 and 102 freshmen students in AY 2011–12. The intervention group (IG) consisted of 88 freshmen students in AY 2012–13. Intervention: The prevention program ran during 1 AY and had 2 main components: an injury awareness program (information brochure, theoretical course, posters, website, technical training) and the application of active strategies (warm-up, cool-down, stretching, dynamic stabilization, functional strength and core stability). Main outcome measurements: Injury risk and incidence rate were the primary outcomes. Functional performance of Lateral Step Down (LSD) and Single Leg Hop and Hold for Distance (SLHHD), self-reported behaviour, consciousness, motivation and knowledge towards injury prevention were secondary outcomes. Results: The IG had a lower injury risk (0.77 Vs. 0.89) and incidence rate (2.34 Vs. 2.72) than the CG. Self-reported behaviour (P<.01), consciousness (P<.01) and knowledge (P=.01) towards injury prevention and functional performance of LSD (P<.01) and SLHHD (P<.01) were significantly better after the intervention. Conclusions: An intervention for the prevention of injuries to the lower limbs in PETE students is efficacious, but more feasibility studies are needed.